2012
DOI: 10.1017/s0954579411000770
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' depressive symptoms and children's facial emotions: Examining the depression–inhibition hypothesis

Abstract: Vibrant expression of emotion is the principal means infants and young children use to elicit appropriate and timely caregiving, stimulation, and support. This study examined the depression-inhibition hypothesis: that declines in mothers' support as their depressive symptoms increase inhibit children's emotional communication. Ninety-four mothers and their 14- to 27-month-olds interacted in a university playroom. Based on microanalytic coding of discrete facial displays, results supported three components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 79 publications
3
37
2
Order By: Relevance
“…A parallel process may apply in the present study where infants were tasked with interactive repair. Thus, consistent with the depression–inhibition hypothesis (Dix et al., ), it can be argued that in the process of recovery following DT, passivity may be an indicator of emotion dysregulation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A parallel process may apply in the present study where infants were tasked with interactive repair. Thus, consistent with the depression–inhibition hypothesis (Dix et al., ), it can be argued that in the process of recovery following DT, passivity may be an indicator of emotion dysregulation.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, we considered outcomes in relation to mothers' depression symptoms. Research on infants' responses during DT found maternal depression associated with dampened expressions of distress (Hart & Behrens, in press; Hart, Field, Letourneau & Del Valle, ), and research on emotion regulation found these capacities diminished among children of depressed mothers (Dix et al., ; Manian & Bornstein, ; Maughan et al., ; Silk et al., ). These findings led us to expect that a similar pattern would be discernible in infants.…”
Section: Emotion Regulation In Response To Other Challenging Conditionsmentioning
confidence: 99%
“…Children may attribute such mother‐focused behavior to hostile intentions, focus processing on their own unmet needs (Hoffman, ), and develop representations dominated by coercive behavior and its short‐term effectiveness. Children, in turn, react with negative emotion (Maccoby & Martin, ), withdrawal (Dix, Meunier, Lusk, & Perfect, ; Yan & Dix, ), or increasingly coercive demands (Shaw et al., ), which focuses their processing on their own self‐oriented intentions, justifications for their negativity in mothers' negative intentions, and the necessity of coercion for eliciting maternal attention (Shaw et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced contact with mother was especially apparent in infants of depressed mothers who also displayed intrusive interactive behavior during floor play (Hart et al 2003). In the context of maternal depression, infants' behavioral inhibition, facial inexpressiveness, and general passivity have been interpreted as indicators of regulatory maladaptation (Dix et al 2012;Feng et al 2008;Field et al 1986;Silk et al 2006). This interpretation was also applied to the flat pattern of response that was elicited in these infants in response to differential treatment.…”
Section: Contextual Influences On Individual Differencesmentioning
confidence: 99%